Synthesis, characterization and reactivity of complex tricyclic oxonium ions, proposed intermediates in natural product biosynthesis - Chan, HSS; Nguyen, QNN; Paton, RS; Burton, JW (American Chemical Society, 2019)
Reactive intermediates frequently play significant roles in the biosynthesis of numerous classes of natural products although the direct observation of these biosynthetically relevant species is rare. We present here direct evidence for the existence of complex, thermally unstable, tricyclic oxonium ions that have been postulated as key reactive intermediates in the biosyn-thesis of numerous halogenated natural products from Laurencia species. Evidence for their existence comes from full characterization of these oxonium ions by low temperature NMR spectroscopy supported by DFT calculations, coupled with the direct generation of ten natural products on exposure of the oxonium ions to various nucleophiles.